2009
DOI: 10.1364/oe.17.020885
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced 2D-image upconversion using solid-state lasers

Abstract: Based on enhanced upconversion, we demonstrate a highly efficient method for converting a full image from one part of the electromagnetic spectrum into a new desired wavelength region. By illuminating a metal transmission mask with a 765 nm Gaussian beam to create an image and subsequently focusing the image inside a nonlinear PPKTP crystal located in the high intra-cavity field of a 1342 nm solid-state Nd:YVO 4 laser, an upconverted image at 488 nm is generated. We have experimentally achieved an upconversion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
64
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(66 citation statements)
references
References 12 publications
0
64
0
2
Order By: Relevance
“…Also the demonstrated image resolutions were limited to approximately 20x20 image elements. In recent work, the present authors have shown 6 orders of magnitude higher conversion efficiencies [5], and more than 3 orders of magnitude higher resolution [6], thus making the idea of having an efficient device based on these principles much less unthinkable. In this work, we will discuss how to optimize another important parameter for upconversion, namely the bandwidth acceptance.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…Also the demonstrated image resolutions were limited to approximately 20x20 image elements. In recent work, the present authors have shown 6 orders of magnitude higher conversion efficiencies [5], and more than 3 orders of magnitude higher resolution [6], thus making the idea of having an efficient device based on these principles much less unthinkable. In this work, we will discuss how to optimize another important parameter for upconversion, namely the bandwidth acceptance.…”
Section: Introductionmentioning
confidence: 75%
“…A full numerical analysis reveals that in this situation the FWHM bandwidth will be ~225 nm for a 10 mm long crystal. Our recent improvements on quantum efficiency [5] and obtainable resolution [6] give promise of an efficient infrared imaging system based on an image upconversion module. Using the principles described here makes it possible to design the effective bandwidth of the upconversion module.…”
Section: Theorymentioning
confidence: 99%
“…11 (b), which was in good agreement with the experimental result. The image blurring was attributed to the spatial filtering relating to the point spread function in the upconversion imaging system [7]. To improve the resolution, large pump beam profile at the Fourier plane would be better to enwrap the transformed object field as much as possible.…”
Section: Ultrasensitive Infrared Imagingmentioning
confidence: 99%
“…One promising application of the singlephoton frequency upconversion is converting the infrared photons to the desired spectral regime (usually visible regime) where the high performance detectors are available for sensitive detections [3][4][5][6]. The infrared single-photon frequency upconversion detection technique has been successfully used in a variety of applications, including infrared imaging [7] and infrared ultra-sensitive spectroscopy [8,9]. Additionally, such upconversion detector has greatly benefited the applications stringently requiring efficient photon detection in optical quantum computation and communication [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…However, inefficiency in the upconversion process was prohibitive, and consequently image upconversion was abandoned [3] as a means to facilitate infrared imaging. Recently we have demonstrated approximately 25% quantum efficiency upconversion of 2-D images using coherent illumination of the object [4].…”
Section: Introductionmentioning
confidence: 99%